Politics and Religion: Identifying the Correlates of Support for Merging the Public and Separate School Systems in Ontario - Davidson, Adrienne; Lucas, Jack; McGregor, Michael (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
This article explores the factors associated with support for a merger of Ontario’s two publicly funded school systems (secular and Catholic). Drawing upon survey data from over 2,000 Ontarians, it investigates the sociodemographic and attitudinal correlates of opinions toward school system reform. We find evidence that both political attitudes and religious identities are associated with school system attitudes, but that religious identity—specifically Catholicism—has a much more powerful impact. Our findings suggest that coalitions of support and opposition to a school system merger in Ontario are complex and not driven by a single obvious cleavage. Keywords: religious education, public opinion, Ontario